1 NEUROPEPTIDEY LEVELS EFFECT ON BLOOD PRESSURE IN CHRONIC KIDNEY DISEASE PATIENTS WITH HYPERTENSION. (May 2022) - Muzasti, Riri Andri; Wendy,; Loesnihari, Ricke
Abstract : Background: Impaired kidney function in Chronic Kidney Disease (CKD) results in increase sympathetic nerve activation, therefore CKD patients often experience hypertension (Ht). Increased sympathetic nerve tone is mediated by increment of sympathetic neurotransmitter which is Neuropeptide Y (NPY). Objective: this study aims to identify Neuropeptide (NPY) levels effect on blood pressure (BP) in CKD patients with hypertension and compare with healthy population. Methods: This case-control study involved 43 CKD patients with regular hemodialysis, 20 non-dialysis CKD stage 1-5 patients and 25 healthy controls. NPY levels were checked by enzyme-linked immunosorbent assay (ELISA). It said to be significant if p value < 0.05. Results: This study shows that NPY levels have a significant effect on BP. Patients with Ht grade II had higher NPY levels (885.80 ng/L) than Ht grade I (423.18 ng/L) or controlled Ht (464.06 ng/L) (p=0.024), but it was higher in controlled (937.56 ng/L) than CKD patients (617.14 ng/L) (p=0.06). Conclusions: > NPY levels affect BP. It seem displays a bidirectional effect in cardiovascular tissue, acting as a cardio-depressant and a cardio-stressor.; lowers BP in healthy populations but increases BP in CKD patients. Further research is needed to prove bidirectional effect of NPY levels and control other factors that influence BP, such as adherence to Ht medication, inflammation, and ages so that the results of this study can represent a large population.